HARMONIOUS INTERACTION OF HUMAN BODY PARTS AND PERSONALITY’S PSYCHOLOGICAL SAFETY - BEJANYAN, ARMEN (Main Issues Of Pedagogy And Psychology, 2015)
The article seeks to identify the place of extreme situationsinthe general system of investigations on psychological aspects of security. A psychological analysis of the extreme situation, its influence on mentality and people behavior is given. The security is regarded as the key conception in social and scientific evaluation of the problem. Security psychology is regarded as a systematized field of psychological knowledge the component of which is considered psychology of extreme situations.